Peningkatan Skil Presentasi Ilmiah Berbahasa Inggris Mahasiswa di Universitas Bumigora Berbasis Strategi Graphic Organizers (GOs) - Dedi Aprianto; Wahyu Kamil Syarifaturrahman; Zainudin Abdussamad; I Nyoman Miyarta Yasa; Nakzim Khalid Siddiq (LPPM Universitas Bumigora, 2022)
The GOs (Graphic Organizers) strategy, which was used in reading comprehension and writing skills research, was then developed into a strategy that could be used as a medium for developing ppt materials. and as an effective and efficient presentation strategy to be used in scientific presentations. This GOs strategy is applied in guiding students in the computer science undergraduate study program in the form of community service (PkM) aimed at increasing student creativity as participants in developing GOs-based creative materials and developing communication skills in delivering scientific presentation materials in class. . This activity was carried out for level I students at Bumigora University with a total of 30 participants. The following are the solutions and steps involved in this PkM activity, namely the use of Graphic Organizers as an effective solution in providing guidance and improvement in conducting scientific presentations carried out by PkM partners. . There are two methods used in providing guidance on the use of the GOs strategy, namely the lecture method where they are given an understanding of the basic concepts of GOs and the simulation method or practice of implementing the Graphic Organizers strategy directly which is carried out by the facilitator/PKM implementation team and followed by the participants. in a participatory manner. The results of this activity show good results and the level of achievement of its use is high. Based on structured observations, it reached a score of 3.7 with a percentage of 73%. The second evaluation was carried out by measuring the perceptions of GOs users, which was a score of 3.8 with a percentage of 77%. Evaluation based on this perception value is high (3.01-4.0).